Quality improvement strategies to enhance care of mechanically ventilated patients and prevent pneumonia - Berba, Regina P.
Background: Ventilator-associated pneumonia (VAP) is a frequently encountered nosocomial infection among critically-ill patients who require mechanical ventilation. It is associated with high morbidity and mortality and greatly increases hospitalization cost and length of stay. Many studies have looked into ways of preventing VAP. The greater challenge is to find the correct combination of strategies to apply these preventive methods into one's setting and decrease the occurrence of VAP. Objectives: To determine the impact of multi-faceted quality improvement (QI) strategies designed to enhance compliance to recommendations in the prevention of ventilator-associated among critically ill patients. Methodology: This study is an eight-month, three-phrase quality improvement investigation using time series analysis. It involved three adult intensive care units at a university hospital. An initial exhaustive review of literature to develop an evidence-based list of recommendations to prevent pneumonia was done through an academic conference in the university with other experts in the fields of Infectious Diseases and Pulmonary Medicine. Three key evidence-based measures know to decrease risk for ventilator-associated pneumonia were chosen and disseminated by various approaches. The three key preventive measures were: proper hand hygiene in the care of mechanically ventilated patients, proper suctioning technique and maintaining head elevation of patients at 30 - 45 degrees. In series, the following were done per ICU: education through interactive lectures with demonstration, written and verbal reminders as well as performance feedback. The interventions involved the major groups of healthcare workers in their respective ICUs and included: nurses, nurse aides, physician-in-training and medical students. Baseline measures were taken on compliance of ICU personnel to hand washing, proper suctioning techniques and putting mechanically ventilated patients on the recommended patient head elevation. The same measure were repeatedly taken by same investigators once a week over the next seven months. During the same period, all mechanically ventilated patients admitted to any of the three ICUs were followed for the development of VAP. The occurrence of VAP was initially evaluated by the physicians-in-charge of the ventilated patients and confirmed by the independent evaluation of two physicians fellows-in-training.